Social Media Mining : Retrieving , Preprocessing Storing and Analyzing Bone Cancer Related Tweets Using R - Mahalakshmi, S (International Journal of Computer Sciences and Engineering, 2025)
Social media provides easily an accessible platform for users to share information. Mining social media has its potential to extract actionable patterns that can be beneficial for business, users,and consumers. Social media data are vast, noisy, unstructured, and dynamic in nature, and thus novel challenges arise. This paper deals with social media mining in which we retrieved tweets ,preprocessed and store it in a csv file in order to compare with ontology related to cancer which is created using protégé. Also analysis made on preprocessed cancer related tweets using R